Ecosystem research in software engineering - Sydorov, N.A. (Інститут програмних систем НАН України, 2025)
The application of the concept of the ecosystem in the software engineering shows the existence of the same problems regarding the definition of the concept of the ecosystem and its use for research that still exists in ecology. Justification for applying the concept of the ecosystem in an area that differs significantly from the ecology area, as in our case, requires researchers to look for analogies. This primarily applies to landscape, energy and matter transfer chains (trophic chains) and nutritional cycles. Until such analogies will be found in software engineering, the ecosystem research is nothing more than system analysis, and the concept of the ecosystem is an attractive concept. The purpose of this position article is to draw the attention of the software engineering community to ecosystem research. Three concepts of ecosystems in ecology, software and software engineering are considered. The composition and essence of ecosystem research in the software engineering are given. The literature review of on the state of ecosystem research in the software was carried out.Problems in programming 2024; 4: 114-124